ANALISIS IMPLEMENTASI GAYA KEPEMIMPINAN DEMOKRATIS PADA KEPEMIMPINAN KEPALA SEKOLAH LANJUTAN TINGKAT ATAS NEGERI 1 KUANTAN MUDIK - Ana Kumala Sari; Lilis Suriani (UIR Press, 2018)
This research aims to know the level of implementation of democratic leadership style in the seniorhigh school number one Kuantan Mudik by the principple. The democratic leadership style, which is measured by the eight indicators that subordinates are given the opportunity to develop creativity, open nature, giving priority to discussion and together need, take a decision in accordance with the objectives of the Organization, actively participate in the activities of the Organization, developing a regeneration, the expansion of cadre recruitment to subordinate further and became the leader of the future, and look at all the problems can be solved by joint efforts. The type of research that is located on senior high school number one Kuantan Mudik Regency Kuantan singingi is a descriptive survey, where prioritizing a list of questionnaire as a tool of data collection and the data collected with this tool then became the main raw material for analyzing the empirical conditions brought the existence of research purposes at locations that are examined. There are three groups of population and sample of this research. And they are the students are 50 people, 15 people teachers, administrative personnels are 3 people. The sampling technique which used is census techniques for administration personnels of the school. Types and file collection techniques used consisted of, primary data, collected with a questionnaire and interview techniques as well as secondary file collected using the technique of observation. While the file analysis technique used is to use a frequency table tools. Based on this analysis, researchers assess the techniques and concluded that the level of implementation of democratic leadership style in the leadership of the head of senior high school number one Kuantan Mudik is in the interval fulfilled.